2021
DOI: 10.2147/ott.s319932
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Treatment Combining Salvage Surgery-Assisted Chemotherapy and Checkpoints Blockade Immunotherapy Achieves Complete Remission on a Recurrent Penile Cancer Patient: A Case Report

Abstract: Penile squamous cell carcinoma (pSCC) is a rare disease in developed countries. pSCC causes a severe health problem and social burden in developing countries. We reported a 49-year-old male recurrent pSCC patient with medium PD-L1 expression and low TMB. The patient obtained complete response after multimodal therapy (MMT). The clinical manifestation is a recurrence in the right groin with nearly ruptured pSCC. He had partial resection of penile cancer plus bilateral groin lymph node dissection and pelvic lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…However, they did not compare the efficacy difference between subgroups of PD-L1 high and low, as researchers did in other types of tumors. Under the light of clinical trials, a few case series and case reports were published, promoting the application of immunotherapy in penile carcinoma and indicating the crucial role of PD-L1 expression in immunotherapy ( 32 35 ). Unfortunately, there were few studies in this area, and more well-designed studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not compare the efficacy difference between subgroups of PD-L1 high and low, as researchers did in other types of tumors. Under the light of clinical trials, a few case series and case reports were published, promoting the application of immunotherapy in penile carcinoma and indicating the crucial role of PD-L1 expression in immunotherapy ( 32 35 ). Unfortunately, there were few studies in this area, and more well-designed studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Comfortingly, most of the patients in these case reports presented with a partial response or a near-complete response. Hu et al [ 18 ] reported a recurrent PSCC patient with medium PD-L1 expression and low TMB who obtained complete response after multimodal therapy that included surgical resection, adjuvant chemotherapy, and continuous sintilimab. It was also recently reported that immunotherapy combined with chemotherapy could have good therapeutic effects in advanced PSCC patients [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, Su et al [15]reported a recurrent metastatic penile SCC patient with positive PD-L1 expression (≥10%) and high TMB of 8.87 (Muts/Mb) who obtained significant response to toripalimab, with progression free survival exceeding 10 months. Hu et al [16]reported a 49-year-old recurrent penile SCC patient with medium PD-L1 expression and low TMB obtained complete response after multimodal therapy, including resection of palliative right inguinal metastases, four cycles of paclitaxel+bleo-mycin+cisplatin and continuous sintilimab. However, it was also recently reported that immunotherapy combined with chemotherapy had good therapeutic effect in advanced penile SCC patients [17,18].…”
Section: Discussionmentioning
confidence: 99%